If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2 = 10 + -2x Reorder the terms: -2 + 4x = 10 + -2x Solving -2 + 4x = 10 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -2 + 4x + 2x = 10 + -2x + 2x Combine like terms: 4x + 2x = 6x -2 + 6x = 10 + -2x + 2x Combine like terms: -2x + 2x = 0 -2 + 6x = 10 + 0 -2 + 6x = 10 Add '2' to each side of the equation. -2 + 2 + 6x = 10 + 2 Combine like terms: -2 + 2 = 0 0 + 6x = 10 + 2 6x = 10 + 2 Combine like terms: 10 + 2 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| 12x-10=3x+40 | | 26.54-p=.5(50-p) | | -4a-36=-4(1+2a) | | 4x^2-9y^2+8x-32=0 | | 3x=66 | | p^2+20p+200=0 | | p^2+20+200=0 | | x^4-4x^3-5x^2+16x+4=0 | | 2(x-2)=36-3x | | 5+10x=68+x | | 5c+7=42 | | 6+0.5(x-2)=9 | | 5+7=42 | | 4x-5=12x-29 | | 7x-6y+2=4x-4y-6 | | 2(a-1)+a=3 | | 6+0.5(x-2)= | | X+3Y=6 | | 4(-5y+1)=-3(-y+6) | | 4x+24=12x-56 | | 8x+9=4x+29 | | 6x+24=15x-66 | | 10x-3=4x-12 | | 12x-16=6x+2 | | 4N-7=13 | | 2(x+3)-5=9 | | 2a^2-4b^2=16 | | 208=2l+2w | | 5x+62=10x+12 | | 12x+5=10x+19 | | f-6=3f+1 | | 7+3d=10-d |